DACT1 overexpression inhibits proliferation, enhances apoptosis, and increases daunorubicin chemosensitivity in KG-1α cells - Ke Zhu; Benchun Jiang; Ying Yang; Rong Hu; Zhuogang Liu (Tumor Biology)
DACT1 has been shown to participate in the development of many types of tumors; however, its role and precise molecular mechanisms in leukemia are unclear. In this study, we investigated the effect of DACT1 on KG-1α leukemia cells to further understand the mechanisms of DACT1-mediated tumor suppression. We transfected a DACT1 expression plasmid to upregulate DACT1 in KG-1α cells and analyzed the resulting phenotypic changes. The results demonstrated that DACT1 overexpression inhibited KG-1α proliferation, increased apoptosis, and arrested cells in the G0/G1 phase. Mechanistically, DACT1 overexpression inhibited Wnt/β-catenin signaling by reducing nuclear β-catenin levels in KG-1α cells. Furthermore, the viability of KG-1α cells transfected with DACT1 was significantly reduced when treated with daunorubicin. We also found that DACT1 reduced P-glycoprotein expression in KG-1α cells. These findings revealed an inhibitory role for DACT1 in leukemogenesis and provided evidence that DACT1 is an attractive target for the development of novel anti-leukemia therapies.